Did DI do it? The impact of a programme designed to improve literacy for Aboriginal and Torres Strait Islander students in remote schools - Guenther, John; Osborne, Samuel (The Australian Journal of Indigenous Education, 2020)
Abstract Over the 10 years of ‘Closing the Gap’, several interventions designed to improve outcomes for Aboriginal and Torres Strait Islander students have been trialled. In 2014 the Australian Government announced the ‘Flexible Literacy for Remote Primary Schools Programme’ (FLFRPSP) which was designed primarily to improve the literacy outcomes of students in remote schools with mostly Aboriginal and Torres Strait Islander students. The programme, using Direct Instruction (DI) or Explicit Direct Instruction, was extended to 2019 with more than $30 million invested. By 2017, 34 remote schools were participating in the Northern Territory, Queensland and Western Australia. This paper analyses My School data for 25 ‘very remote’ FLFRPSP schools with more than 80% Aboriginal or Torres Strait Islander students. It considers Year 3 and 5 NAPLAN reading results and attendance rates for participating and non-participating primary schools in the 3 years before the programme's implementation and compares them with results since. Findings show that, compared to very remote schools without FLFRPSP, the programme has not improved students' literacy abilities and results. Attendance rates for intervention schools have declined faster than for non-intervention schools. The paper questions the ethics of policy implementation and the role of evidence as a tool for accountability.